Middle East Oil Show and Conference 1997
DOI: 10.2118/37795-ms
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Welltests in Determining the Drive Mechanism and Threshold Pressures Between Three Communicating Reservoirs

Abstract: SPE Members Abstract The implementation of a welltesting program of Build Up and Draw Down tests conducted on wells producing with high GOR from a thin tight oil zone has revealed a unique and consistent communication pattern between three communicating reservoirs. Analysis of the tests showed conflicting response; in Draw-Downs, for instance, Constant Pressure Boundaries (CPB) were detected, whereas in Build Ups, barriers were encountered for the same well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…• Within a given reservoir, pressure-dependent communication across fault planes may start to leak fluids when a sufficient pressure difference--the pressure threshold--is applied to both sides of the fault (Zubari and Al-Awainati, 1997). In the case of Central Haradh's western flank, the threshold pressure concept may be applied to a fault zone vertically linking the hydrostatic Jurassic Arab-D reservoir and a charged shallower aquifer such as the Cretaceous Biyadh (Figure 29).…”
Section: Discussionmentioning
confidence: 99%
“…• Within a given reservoir, pressure-dependent communication across fault planes may start to leak fluids when a sufficient pressure difference--the pressure threshold--is applied to both sides of the fault (Zubari and Al-Awainati, 1997). In the case of Central Haradh's western flank, the threshold pressure concept may be applied to a fault zone vertically linking the hydrostatic Jurassic Arab-D reservoir and a charged shallower aquifer such as the Cretaceous Biyadh (Figure 29).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier attempts to conduct buildups in the gas lifted wells were complete failures due to the noise caused by the gas lift gas in the Early and Middle Time Region. So a new innovative procedure was designed to utilize the gas-lift gas at the wellhead to carry out a falloff test 5,6,7 . A known quantity of gas was injected into the formation over a few days followed by shutting in the well for a falloff test.…”
Section: Well-tests In Ahmadi Reservoirmentioning
confidence: 99%
“…Furthermore, the fault throws and the areas of communication between Ab and the underlying zones controlled the degree of communication and the type of fluids being introduced into the Ab zones. Earlier studies has shown that Aab zone is continuously receiving fluid and pressure support in certain areas from the underlying higher pressure Mauddud zone (which is undergoing gas injection 8,9 ) through an intermediate sandstone layer, the Wara sandstone which exist in the form of erratic sand lenses distributed irregularly all over the field 6,7 .…”
Section: Production Data Analysismentioning
confidence: 99%